Artificial oocyte activation with Ca2+ ionophore improves reproductive outcomes in patients with fertilization failure and poor embryo development in previous ICSI cycles - Ruan, Jing Ling; Liang, Shan Shan; Pan, Jia Ping; Chen, Zhi Qin; Teng, Xiao Ming (Frontiers in Endocrinology, 2023)
Research question: Does artificial oocyte activation (AOA) by a calcium ionophore (ionomycin) improve the previous fertilization failure or poor embryo development of intracytoplasmic sperm injection (ICSI) account for male factor infertility or other infertility causes?Design: This retrospective study involved 114 patients receiving ICSI-AOA in Shanghai First Maternity and Infant Hospital with previous ICSI fertilization failure or poor embryo development. The previous ICSI cycles of the same patients without AOA served as the control group. The fertilization rates, cleavage rates, transferable embryo rates and blastocyst formation rates of the two groups were compared.Additionally, the clinical pregnancy, implantation rate and live birth rates were also compared to assess the efficiency and safety of AOA. Furthermore, two subgroup analyses were performed in this study based on the cause of infertility and the reason for AOA. The fertilization rate, embryonic development potential and clinical outcome were compared among groups.Results: Among 114 ICSI-AOA cycles, the fertilization rate, top-quality embryo rate, implantation rate, clinical pregnancy per patient and live birth rate per patient were improved significantly compared with previous ICSI cycles (p<0.05 to P< 0.001), and the miscarriage rate in the AOA group was significantly lower than that of the control group (p<0.001). In the AOA subgroups based on the cause of infertility, the fertilization rates of each subgroup were significantly improved compared with previous control cycles except for the mixed factor infertility subgroup (p<0.05 to p<0.001). In the AOA subgroups based on the reason for AOA, the fertilization rates of each subgroup were significantly increased compared with those in their previous ICSI cycle without AOA (p<0.001); however, there was no significant difference in the top-quality embryo rate. No significant improvement was found in the implantation 3 rates and the clinical pregnancy rate in each subgroup except for the poor embryo development subgroup.In the 114 AOA cycles, 35 healthy infants (21 singletons and 7 twins) were delivered without major congenital birth defects or malformations.This study showed that AOA with the calcium ionophore ionomycin can improve the reproductive outcomes of patients with previous fertilization failure and poor embryo development after ICSI.